QARAQALPAQ TILINDE BALÍQSHÍLÍQ TARAWÍ TERMINLERINIŃ LEKSIKA-GRAMMATIKALÍQ QURÍLÍSÍ HÁM SEMANTIKALÍQ MÁNISI - Nuranova, S.G. (SCIENCE and SOCIETY, 2024)
In the article, examples and meanings of zoonym component terms in the Karakalpak language were presented. It was interpreted that various characteristics of a person are used in a descriptive way through the zoonym of fish.